Analysis of Academic Stress Levels in UIN Walisongo Semarang Students and Its Impact on Physical Well-Being - Sa'adah, Aulia Muthiatus; Shanie, Arsan (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Analysis of Academic Stress Levels in UIN Walisongo Semarang Students and Its Impact on Physical Well-Being. This research aims to measure the level of academic stress experienced by students in the last two to three weeks of study and to determine the causes and influence on their physical condition. The research was attended by 30 student respondents. The research method used is a quantitative method using the measurement instrument The Perception of Academic Stress Scale (PASS) and questionnaires related to physical condition. The analysis technique used is simple regression analysis and Pearson Product Moment correlation analysis. The research results show that the majority of students (93%) have high levels of academic stress. The burden of coursework and exams is the highest cause of academic stress. And from the regression analysis, the Fcount value was 13.391˃Ftable 4.196 (significant) and the calculated variance proportion was 0.299. This means that academic stress has an influence on physical condition with an influence of 29.9%. The results of the correlation analysis obtained an rcount value of 0.569˃rtable 0.361 (significant). This means that there is a positive relationship/influence, where the higher the level of academic stress, the higher the complaints about physical condition.Keywords: Academic Stress; Student; Physical condition.